Quality of Housing of Collective Farm Families in Sverdlovsk Region and Construction “Boom” of Second Half of 1950-ies - V. N. Mamyachenkov; N. Y. Vlasova; E. L. Molokova (Научный диалог, 2019)
The results of the study of the quality of housing, where one of the largest categories of the population of the Sverdlovsk region - peasants-collective farmers - lived at the end of the 1950-ies of 20th century. The base of the conducted research were the results of statistical surveys of the villagers, which were held in the USSR since the early 1930-ies until the second half of 1960-ies. New archival materials are being put into circulation. It is stated that in the history of the 20th century the housing problem has remained one of the list of those that the Soviet command and administrative system has not been able to solve. It is stated that the issues of provision of housing for rural residents and its quality are practically not covered in the works of Middle Ural social scientists. It is noted that the main researchers’ attention is usually occupied by the material conditions of life of farmers, that is, their income, expenses, as well as the level of consumption. It is declared that by the mid-1950-ies the tension in the housing sector of the country reached its apogee. It is argued that since 1956 a complete modernization of the entire organization of construction business in the USSR had begun. The thesis that the development of urban infrastructure of the Middle Urals in the 1950-ies should not be overestimated is put forward. It is concluded that the Middle Ural village was in clearly the worst conditions by almost all indicators of life of the population, and the construction “boom” of the second half of the 1950-ies had little impact on the volume and quality of its housing stock.